Pemanfaatan Cuka Kayu Sebagai Bahan Pengawet Alami Kayu Pulai (Alstonia scholaris) Terhadap Serangan Jamur (Schizophyllum commune Fires.) - Riana Anggraini; Jauhar Khabibi (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Preserving wood using chemical preservatives has a negative effect on the environment, so preservatives are needed that are more environmentally friendly. Wood vinegar from sawn waste contains potential acid and phenol compounds as natural preservatives. This study aims to assess the effectiveness of tembesu wood vinegar (Fagraea fragrans) and rengas (Gluta renghas) as natural preservatives and analyze the durability of pulai wood (Alstonia scholaris) against Schizophyllum commune Fires. The preservation method is carried out by cold-soaking for 48 hours then proceed with the feeding process with the fungus Schizophyllum commune Fires for 8 weeks. The variables observed were retention value, absorption and penetration of preservatives. The results showed that the retention and absorption value of pulai wood that was soaked with wood vinegar decreased based on the position of the wood part, starting at the base, middle and tip. The value and absorption of tembesu wood vinegar has a greater value than renghas wood vinegar. The results of wood vinegar penetration showed increased values starting from the base, middle, and top of the wood. Renghas wood vinegar is not visible from the penetration result while tembesu wood vinegar is visible from the penetration. The visual checking on the wood samples shows that the both of Renghas and Tembesu wood vinegar can be inhibited the Schizophyllum commune Fires growth.